Effect of rootstock on growth, yield and fruit characteristics in cv. 'Bianca' pistachio (Pistacia vera L.) trees - Caruso T.; Barone E.; Marra F.P.; Sottile F.; La Mantia M.; De Pasquale C. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
This paper, following preliminary field evaluation trials started in 1993, reports a study on the effect of eight different in vitro-propagated clonal rootstocks (P. atlantica and P. integerrima) and one seedling rootstock (P. terebinthus) on the vegetative and productive behaviour of pistachio cultivar 'Bianca'. The trees, budded in 1991, were grown using standard cultural practices for dry-land farming in a sandy clay loam soil, located inland in Sicily. On average, clones of P. integerrima (I-6 and I-2) were the most vigorous rootstocks. Clones of P. atlantica had intermediate vigour. Rootstock significantly affect yield but not fruit weight, kernel to nut ratio, splitting and blanking percentages. The highest yield efficiencies were observed with I-4 and A-3 and A-5, whereas the lowest were obtained with I-6 and I-2 and A-8. Nut shape was significantly affected by the rootstock. Slight differences in leaf mineral content were observed among the tested graft combinations.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)